Resepsi Teks Pararaton: dari Serat ke Novel - Abdul Hakim (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2018)
This paper is ground by the presence of novel Pararaton as a new form of text Pararaton. The problem in this paper is how the Pararaton text is perceived into a novel form. This paper aims to explain the novel differences with the classic Pararaton texts and to show an inversion in the form of a novel that is adapted according to the horizon of today's readers' expectations. To address this problem, this paper uses Hans Robert Jauss' reception theory and phenomenology methods. This paper shows some analysis results.  First, the novel Pararaton shows richer with narrative detailing than the Pararaton text. Secondly, Novel Pararaton also shows the creation of the depiction of Ken Arok, Ken Dedes, and Tunggul Ametung. The creations relate to the expectations horizon of today's society. Third, Pararaton's novel as a reflection of Pararatonic classical texts, figures or characterizations, story settings, and grooves. Fourth, the novel Pararaton presented with a full ethical narrative in describing the characters Tunggul Ametung and Ken Arok.Key word: novel Pararaton, reception, the expectation horizon, inversion